Nghiên cứu lý thuyết hoạt tính xúc tác của axetylcholines ở người - Thọ, Nguyễn Hữu; Thu Cúc, Tống Thị (Vietnam Journal of Chemistry, 2015)
Homo sapiens’ acetylcholinesterase was docked with the substrate (acetylcholine) to find the most favorite binding sites. The state in which acetylcholine is located above Ser(203) in the active site gorge has the lowest binding energy. The mechanism of the hydrolysis of acetylcholine (a neurotransmitter) catalyzed by Homo sapiens’ enzyme was verified on structure and energy using QM/MM method. Structures of intermediates (state when substrate approaches active site, enzyme - substrate complex, and state when choline is eliminated) were optimized. The transition states were located with the estimation for the activation energy was 11.943 kcal/mol for the formation of enzyme - substrate complex, and 0.032 kcal/mol for the elimination of choline.